3, 4‐Dimethoxychalcone induces autophagy through activation of the transcription factors TFE3 and TFEB. Issue 11 (14th October 2019) - Chen, Guo; Xie, Wei; Nah, Jihoon; Sauvat, Allan; Liu, Peng; Pietrocola, Federico; Sica, Valentina; Carmona‐Gutierrez, Didac; Zimmermann, Andreas; Pendl, Tobias; Tadic, Jelena; Bergmann, Martina; et al.
Abstract: Caloric restriction mimetics (CRMs) are natural or synthetic compounds that mimic the health‐promoting and longevity‐extending effects of caloric restriction. CRMs provoke the deacetylation of cellular proteins coupled to an increase in autophagic flux in the absence of toxicity. Here, we report the identification of a novel candidate CRM, namely 3, 4‐dimethoxychalcone (3, 4‐DC), among a library of polyphenols. When added to several different human cell lines, 3, 4‐DC induced the deacetylation of cytoplasmic proteins and stimulated autophagic flux. At difference with other well‐characterized CRMs, 3, 4‐DC, however, required transcription factor EB (TFEB)‐ and E3 (TFE3)‐dependent gene transcription and mRNA translation to trigger autophagy. 3, 4‐DC stimulated the translocation of TFEB and TFE3 into nuclei both in vitro and in vivo, in hepatocytes and cardiomyocytes. 3, 4‐DC induced autophagy in vitro and in mouse organs, mediated autophagy‐dependent cardioprotective effects, and improved the efficacy of anticancer chemotherapy in vivo . Altogether, our results suggest that 3, 4‐DC is a novel CRM with a previously unrecognized mode of action. Synopsis: From a library of polyphenols and polyamines, the 3, 4‐dimethoxychalcone (3, 4‐DC) was screened and identified as a caloric restriction mimetic (CRM) that induces autophagy through TFEB and TFE3 and results in cardioprotection and improved efficacy of anticancer chemotherapy in mice. 3, 4‐DC induces all hallmarks of caloric restriction mimicry, i.e. the combination of autophagy, reduced protein acetylation and absence of toxicity. 3, 4‐DC induces autophagy in a TFEB‐ and TFE3‐regulated, transcription and translation‐dependent manner. 3, 4‐DC causes cardioprotection and enhances anticancer effects of chemotherapy in an autophagy‐dependent fashion in vivo in mice. Abstract : From a library of polyphenols and polyamines, the 3, 4‐dimethoxychalcone (3, 4‐DC) was screened and identified as a caloric restriction mimetic (CRM) that induces autophagy through TFEB and TFE3 and results in cardioprotection and improved efficacy of anticancer chemotherapy in mice.